Decentralizing Governance : Emerging Concepts and Practices - Rondinelli, Dennis A.; Cheema, G. Shabbir (Book collections on Project MUSE., 2007)
"Assesses the emerging concepts of decentralization (devolution, empowerment, capacity building, and democratic governance) in different contexts and regions. Details the factors driving the movement, including political changes such as the fall of the Iron Curtain and the ascendance of democracy; economic factors such as globalization and outsourcing; and technological advances"--Provided by publisher